Hakikat Manusia dan Relevansinya terhadap Isu-isu Kemanusiaan: Analisis Komparatif Filsafat Politik Thomas Hobbes dan John Locke - Darussalam, Fajrul Ilmy; Indra, Andi Batara; Rahman, Saifur (Media: Jurnal Filsafat dan Teologi, 2024)
Humans with all their attachments seem to increasingly emphasize that humans are basically very complex creatures. This research aims to re-examine the points of contact and differences in the views of John Locke and Thomas Hobbes regarding human nature and explore the extent of their relevance to contemporary humanitarian issues. This research is library research using a comparative study model, with several methodical elements such as interpretation, internal coherence, holistic, comparison, and description. The results are 1) Locke and Hobbes' ideas have fundamental similarities in the state of nature and the social contract, namely natural rights that are inherent in every individual and require another authority for the common good; 2) Locke and Hobbes' ideas also have differences. Each other in natural conditions and the social contract, namely the source and form of authority or legitimacy that is formed, and 3) both become the main pattern in the development of the concept of government or state related to humanitarian issues such as human rights, freedom and authority.